The The Influence of Class Shift on Achieving Semantic Meaning in the English-Indonesian Translation of Yule’s Pragmatics - Taufiqi, Muhammad Aulia; Hartono, Rudi; Mujiyanto, Januarius (Universitas Negeri Semarang, 2019)
The important of translation can be seen in our daily life. Translation can be found in many aspects of our life such as books, newspaper, magazines, novel, comics, even movies. One important aspect in translation study is class shift. Class shift deals with the changing of word classes in source language to the target language. Hence one language and others are different, this study aimed to know the influence of class shift on achieving semantic meaning in the English-Indonesian translation of Yule’s pragmatics. Qualitative research is the type of this research and descriptive qualitative as research design. There are three chapters of the book which are chosen randomly as the data on this study. The total number of data is 98 from those three chapters. The results of the study show that there are seven types of class shift which are found in this study such as adjective to adverb, adjective to noun, adjective to verb, adverb to adjective, adverb to noun, adverb to verb, and verb to adjective. There are two types of class shift which often appear in this study. Those are adjective to noun and adverb to adjective. Class shift can be occurred anytime. The occurrence of class shifts does not guarantee anything in achieving meaning of a sentence.